Análisis de la distribución de planta del área de fundición de la empresa Cedal Aluminio S.A. Latacunga, para generar una propuesta de redistribución. - Chanaluisa Chiliquinga, Edgar Javier (2019)
The purpose of this research work is to study the distribution of the facilities comprised by the Casting Area in the Ecuadorian Aluminum Corporation CEDAL S.A. Latacunga, dedicated to the production of aluminum ingots from the scrap smelting process recovered from the extrusion process and rejected profiling. Cedal S.A is considered one of the important companies in the international market, as well as being one of the leading companies in the Ecuadorian commercial scope for the type of metallurgical industry. In the first instance during the research process, we proceed to study the design of the layout in the area, for which it requires knowing: the sequence of the production process, the production methods followed by the times and distances used, as well as the distinction of equipment and machines. that intervene to obtain the final product which will allow knowing the necessary surface, consequently it is determined that there are sub processes with productive deficiency due to the high investment of time. On the other hand it is considered that transport is carried out with very long distances generating unproductive times, in addition to the spaces are not used correctly and does not comply with any current legal regulations. Finally, with the application of the Guerchet and SLP method, and with the help of the Win QSB software, an efficient redistribution is sought and the need for an approximate area of 2,563,248 m2 was obtained with an investment for changes and adjustments of $ 136,820, 00 with a return period of approximately 2 months, productivity would rise by 4%.